Evaluation of acute kidney injury with oxidative stress biomarkers and Renal Resistive Index after cardiac surgery. Issue 3 (4th May 2021) - Kararmaz, Alper; Arslantas, Mustafa Kemal; Aksu, Ugur; Ulugol, Halim; Cinel, Ismail; Toraman, Fevzi
Abstract: Background: We investigated whether cardiopulmonary bypass (CPB) related oxidative stress mediated glycocalyx degradation can cause an increase in renal resistive index (RRI) or postoperative AKI. Additionally, to evaluate whether RRI and early postoperative serum cystatin C levels could improve the prediction sensitivity of acute kidney injury (AKI). Methods: Forty-two patients undergoing cardiac surgery were included in this prospective observational study. RRI was measured pre-operatively and in the cardiac intensive care unit. Blood samples were collected for analyzing of cellular injury biomarkers at preoperative and postoperative second hours. We determined areas under the receiver operating characteristic curve (AUC) and odds ratios for postoperative biomarkers and RRI to predict AKI. Results: While postoperative cystatin C level (AUC: 0.902, 95% CI = 0.79–1.00, p < .001) and RRI (AUC: 0.748, 95% CI = 0.56–0.93, p = .023) have diagnostic and predictive value in the prediction of AKI, we could not identify any relation between products of oxidative stress and the glycocalyx degradation and AKI. Conclusion: These data suggest that CPB leads to structural and oxidative changes at the protein level and the integrity of glycocalyx is disturbing, but these changes are not specific to kidney injury. Our data suggest that serum cystatin C level and RRI could be used as an early biomarker for postoperative AKI after cardiac surgery.